The Continuum: A New Approach to the Place of Tort in a Contractual Matrix - Thomson, William (Victoria University of Wellington Law Review, 2006)
This paper discusses the approach that is taken in New Zealand to determining whether a tortious duty of care can exist across a contractual matrix. The two step approach adopted in the recent decision of the Court of Appeal in Rolls-Royce NZ Ltd v Carter Holt Harvey Ltd is fundamentally agreed with. A continuum is suggested for the balancing exercise in the tortious duty of care inquiry. This rationalises past cases and will hopefully provide guidance for future ones.